Inducing cooperation with emotion - who is affected? - Manja Gärtner; Gustav Tinghög; Daniel Västfjäll (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
We study the effects of dual processing differences that arise from the state level (through experimental manipulation of the decision mode), the trait level (using individual difference measures of the decision mode), and their interaction on cooperative behavior. In a survey experiment with a representative sample of the Swedish population (N = 1,828), we elicited the individuals' primary decision mode and experimentally varied whether individuals could rely on their preferred mode or were induced to rely either on emotion or reason. Cooperation was measured across a series of commonly used and incentivized games (prisoner's dilemma game, public goods game, trust game, dictator game). At the state level, our results show that average cooperation rates increased when emotions were induced rather than reason. At the trait level, our results show that individual decision modes and cooperation rates were not correlated when subjects could rely on their primary mode, but traits interacted with our processing manipulation: Experimentally inducing emotions increased cooperation among individuals who otherwise rely primarily on reason, but not among individuals who already rely primarily on emotion. These findings suggest that individuals integrate their traits with emotion-based states by substituting their trait rather than enhancing it. Thus, who is affected by emotions in their decision to cooperate crucially depends on state-trait interactions at the point of decision.
Keywords: C71; C91; D91; 330; cooperation; intuition; emotion; reason; experiment